2021
DOI: 10.1016/j.jhazmat.2020.123694
|View full text |Cite
|
Sign up to set email alerts
|

Smoke toxicity of rainscreen façades

Abstract: The toxic smoke production of four rainscreen façade systems were compared during large-scale fire performance testing on a reduced height BS 8414 test wall. Systems comprising 'non-combustible' aluminium composite material (ACM) with polyisocyanurate (PIR), phenolic foam (PF) and stone wool (SW) insulation, and polyethylene-filled ACM with PIR insulation were tested. Smoke toxicity was measured by sampling gases at two points -the exhaust duct of the main test room and an additional 'kitchen vent', which conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The combustion of polymer materials produces a certain degree of smoke. According to the long-term accumulation of various types of fire data, the smoke and toxicity produced by combustion are the main causes of human death, and the harm is often more serious than the flame and heat generated during combustion [16][17][18]. The smoke density test is the main method to evaluate the smoke production performance of materials, the larger the maximum light absorption rate, the greater the amount of smoke produced during combustion [19].…”
Section: Smoke Emission Density Analysismentioning
confidence: 99%
“…The combustion of polymer materials produces a certain degree of smoke. According to the long-term accumulation of various types of fire data, the smoke and toxicity produced by combustion are the main causes of human death, and the harm is often more serious than the flame and heat generated during combustion [16][17][18]. The smoke density test is the main method to evaluate the smoke production performance of materials, the larger the maximum light absorption rate, the greater the amount of smoke produced during combustion [19].…”
Section: Smoke Emission Density Analysismentioning
confidence: 99%
“…Various studies identified fire behaviour within cavity geometries [1][2][3][4][5][6] with their own focus, and thus, could not identify the generalized fire behaviour in cavities. Most often, in these studies, clear indications were not given for the severity of cavity fire scenarios compared with open-fire scenarios to highlight the importance of considering cavity fire in building designs [2][3][4]7,8]. Several research studies attempted to develop expressions to predict fire behavior within particular cavity types [4,5,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their validity must be identified by comparing them with other studies. A range of fire safety issues associated with cavity fire spread have been identified by different studies [3,8,14,15]. However, various parameters govern these fire risks, and studies often consider individual parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The study found PE-aluminium composite material (ACM) to exhibit 55 times peak heat release rates and 70 times total heat release compared to the least flammable panel with a possibility of rapid-fire spread in the external cladding, releasing significant toxic emissions. Two recent publications by Peck et al [33] carried out testing in a large-scale BS 8414 test wall and BS 8414-1 façade flammability tests to compare the smoke toxicity and burning behaviour of four different types of rain-screen façade systems (ACM) with polyisocyanurate (PIR), phenolic foam (PhF), stone wool (SW) insulation, and polyethylene (PE) filled with PIR insulation fillings. The smoke toxicity study found that occupants exposed to emissions from PIR and PF are predicted to collapse within a few minutes of exposure, which will impede their ability to escape, leading to inhalation of lethal concentrations of asphyxiant gases (CO and HCN) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent publications by Peck et al [33] carried out testing in a large-scale BS 8414 test wall and BS 8414-1 façade flammability tests to compare the smoke toxicity and burning behaviour of four different types of rain-screen façade systems (ACM) with polyisocyanurate (PIR), phenolic foam (PhF), stone wool (SW) insulation, and polyethylene (PE) filled with PIR insulation fillings. The smoke toxicity study found that occupants exposed to emissions from PIR and PF are predicted to collapse within a few minutes of exposure, which will impede their ability to escape, leading to inhalation of lethal concentrations of asphyxiant gases (CO and HCN) [33]. Furthermore, in the flammability test, the façade system melted away, losing its structural integrity and contributing to rapid flame spread [34].…”
Section: Introductionmentioning
confidence: 99%